New development: Enhancing regional innovation capabilities through formal public service communities of practice. Issue 8 (17th November 2022) - Walpole, Gary; Bacon, Emily; Beverley, Katie; De Laurentis, Carla; Renfrew, Kay; Rudd, Jennifer
IMPACT: The circular economy (CE) involves sharing, leasing, reusing, repairing, refurbishing and recycling existing materials and products for as long as possible—moving away from the traditional linear economy. The Circular Economy Innovation Community (CEIC) project, presented in this article, developed a novel programme to create regional inter-organizational innovation communities of practice for public service organizations across a region. Participants were introduced to contemporary tools and techniques to enable their organizations to reduce their carbon footprints, reduce costs and enhance service levels. The authors describe the way that the CEIC project has been able to create sustainable innovation communities of 'change-makers'—enhancing regional innovation capabilities and supporting the transition to a CE.